2008
DOI: 10.1098/rstb.2008.0107
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping neuronal circuits in addiction and obesity: evidence of systems pathology

Abstract: Drugs and food exert their reinforcing effects in part by increasing dopamine (DA) in limbic regions, which has generated interest in understanding how drug abuse/addiction relates to obesity. Here, we integrate findings from positron emission tomography imaging studies on DA's role in drug abuse/addiction and in obesity and propose a common model for these two conditions. Both in abuse/addiction and in obesity, there is an enhanced value of one type of reinforcer (drugs and food, respectively) at the expense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
561
2
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 714 publications
(604 citation statements)
references
References 57 publications
26
561
2
15
Order By: Relevance
“…In animals and humans, obesity and intake of high-fat or high-sugar diets are associated with decreased dopamine D2 receptor expression and binding, decreased dopamine transporter function, and reduced thresholds for brain stimulation reward [91][92][93][94]. These changes may decrease the reward value of food, relative to control subjects, and this may drive people to overconsume to compensate.…”
Section: Implications For Obesity and Human Feeding Behaviourmentioning
confidence: 99%
“…In animals and humans, obesity and intake of high-fat or high-sugar diets are associated with decreased dopamine D2 receptor expression and binding, decreased dopamine transporter function, and reduced thresholds for brain stimulation reward [91][92][93][94]. These changes may decrease the reward value of food, relative to control subjects, and this may drive people to overconsume to compensate.…”
Section: Implications For Obesity and Human Feeding Behaviourmentioning
confidence: 99%
“…Since all classes of misused drugs -alcohol, tobacco, stimulants, pain killers, tranquilizersare believed to usurp the naturally occurring reward pathways meant to help control food (and thus nutrient/energy) intake [1], substance addiction has the potential to induce clinical and subclinical malnutrition states. In addition, psychological desire for food is altered in individuals misusing substances.…”
Section: Interaction Of Addictive Disorders With Medical Nutritional mentioning
confidence: 99%
“…Volkow et al [1] reviewed the similarities in neural circuitries underlying motivation to acquire and ingest food and drugs. Common neurotransmitters involved in these processes include mesolimbic dopamine and opioid circuits.…”
Section: Interaction Of Addictive Disorders and Food Intake Regulationmentioning
confidence: 99%
“…It has been recognized that the resemblance may reflect the involvement of the same neural systems, including those implicated in regulatory self-control and reward in both groups of disorders. It has been widely demonstrated that the DAergic "meso-limbic" reward system has a crucial role not only in the passage from an occasional use to an abuse of drugs, but also in the transition from a normal feeding to a maladaptive compulsive eating behavior [1,3,[6][7][8]. Human studies showed that DAergic release correlates with the reward from both drug and food use [9,10].…”
mentioning
confidence: 99%
“…Genetic variants in eating disorders have been investigated [14][15][16], and the Taq1A (minor) allele of DA receptors D2 (DRD2) gene is associated with many of substance-misuse disorders [16][17][18]. Furthermore, it has been defined that lower levels of striatal DRD2s can signal a "reward-deficiency" state leading to over-seeking/ taking behaviors [7], thus suggesting that low DRD2 availability could be a formative genetic risk factor in compulsive food seeking/ taking behavior [3]. Finally, is conceivable that gene-environment interactions are able to induce neuroadaptations in several brain areas related to substance use disorders, such as the DAergic "meso-limbic" reward system.…”
mentioning
confidence: 99%